Enhancing Children’s Emotion Regulation Through Educational Puppets With QR Code Technology - Gunawan, Anjanette Amelia; Tan, Edwin; Angela, Felice; Fatiha, Salsabila Zahrani; Kartasasmita, Sandy (International Journal of Education, Information Technology, and Others, 2025)
Children aged 4–6 years often encounter challenges in recognizing, understanding, and managing their emotions, which underscores the importance of engaging and interactive learning media. Puppets have long served as effective educational tools that support children’s social and emotional development. This study aims to design and evaluate a QR code–based emotion puppet as a medium to assist early childhood in emotional regulation. Referring to Paul Ekman’s six basic emotions—happiness, sadness, anger, fear, surprise, and disgust—the puppet introduces these emotions through features linked to QR codes that direct users to educational videos. These videos provide interactive guidance on identifying emotions, expressing them appropriately, and applying suitable regulation strategies. A quasi-experimental approach was employed with 19 preschool children participating, though only 12 valid data sets were used for analysis. The findings reveal that the intervention led to improvements in children’s abilities to recognize, express, and regulate their emotions more effectively. Children also became more open in communicating their feelings with others. Additionally, the interactive puppet successfully attracted children’s interest in the emotional learning process, promoting deeper engagement in exploring emotions. Overall, the results suggest that the QR code–based emotion puppet is an effective educational medium that supports emotional regulation and helps strengthen social skills in early childhood.